Insurance coverage in unstable region: Managing insurance claim risk amid Kashmir's political landscape - Punoo, Aamir Altaf; Ota, Mahadev; Mohammed, Shariq; Azad, Imran; Khan, Mohammad Shahfaraz; Dar, Amir Ahmad (Edelweiss Applied Science and Technology, 2024)
This study investigates the impact of prolonged political unrest on insurance claim amounts in Kashmir. It examines the behavior and coverage provided by insurance companies in high-risk areas, focusing on the hazards and perils associated with terrorism and political uncertainty. By analyzing historical data on political violence and terrorism in Kashmir, the study reveals significant patterns and relationships through descriptive statistics. The findings demonstrate that higher levels of political violence and terrorism lead to increased losses for insurers. Moreover, the study underscores the necessity of tailoring insurance coverage to the specific risks in unstable regions. It suggests employing time series analysis for more accurate pricing of insurance policies during periods of political instability. These insights offer practical implications for insurance companies, policymakers, and stakeholders, facilitating more effective risk assessment, pricing, and risk management strategies in volatile areas. In addition to outlining general customer requirements, the study discusses the measures and regulations needed for commercial insurers to provide economical services in such contexts. This comprehensive analysis enhances the understanding of the effects of abnormal situations like prolonged political unrest in Kashmir. Ultimately, the study proposes the integration of time series analysis into insurance pricing models to better navigate periods of political instability.